Kinase Inhibitors with Redox and Anti-inflammatory Activities - Ivanovska, Nina; Saso, Luciano; Dimitrov, Petya (Current Topics in Medicinal Chemistry, 2015)
The development of inflammatory immune response is related to an activation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-ΚB) signaling. The intracellular molecules from this pathway are sensitive to the alterations in the microenvironment. The changes in cellular redox state, proliferation, gene expression pattern and genomic stability during inflammation induce the activation of non-canonical and atypical NK-ΚB signaling increasing the crosstalk with molecules involved in neddylation, cell cycle checkpoints regulation and DNA repair. This review article describes the reactive oxygen species (ROS)-sensitive kinases from the NF-ΚB pathway and presents the effects of their suppression by small kinase inhibitors. It illustrates that selective targeting of the redox sensor molecules from the inflammatory NK- ΚB cascades can influence cell survival and metabolism as well. We think that this issue is important when evaluating the drug efficacy in clinical studies and their side effects.
Keywords: Ataxia-telangiectasia (A-T) mutated kinase